PELATIHAN PEMANFAATAN TEKNOLOGI INFORMASI DAN PENGGUNAAN DIGITAL SAFETY DI DESA CIMARANTEN KUNINGAN - Sugiharto, Tito; Panji Novantara; Tata Sutabri (Politeknik Negeri Sriwijaya, 2024)
The training on the utilization of information technology and the use of digital safety in Cimaranten Village, Kuningan Regency, aims to improve the digital literacy of the community and increase awareness and skills in maintaining digital security. This activity was motivated by the lack of understanding and skills of the village community in using information technology, as well as the high risk of digital crime faced due to lack of knowledge about digital safety. The methodology used in this training includes preliminary studies, activity planning, development of training materials, training implementation, evaluation, and monitoring. A preliminary study was conducted to identify the needs and initial conditions of the community. The results of the training showed a significant increase in digital literacy and understanding of digital security among participants. Before the training, most participants had a very basic understanding of information technology and were unaware of digital security risks. After the training, participants were able to use digital devices for daily purposes and had a better understanding of how to protect themselves from digital crime. Participant satisfaction evaluation showed that 80% understood digital literacy, 84% mastered information technology and 76% understood digital safety, in addition to the participants felt that the material presented was very useful and the teaching methods were effective. The expected long-term impact of this training is the improvement of the quality of life of the Cimaranten Village community through better and safer utilization of information technology, as well as increased economic and educational opportunities through technology adoption